PERBANDINGAN AKURASI METODE ARBITRAGE PRICING THEORY DAN THREE FACTOR MODEL DALAM MENGESTIMASI RETURN SAHAM: (Studi Pada Perusahaan Sub Sektor Farmasi Yang Listing di BEI Periode Frbruari 2020 – Desember 2022) - Nur Arifah; Immas Nurhayati; Renea Shinta Aminda (Cross-border, 2023)
The purpose of this study was to determine the accuracy of the Arbitrage Pricing Theory (APT) and Three Factor Model (TFM) models in estimating stock returns in pharmaceutical sub-sector companies for the period February 2020 – December 2022. The population of this study were all stocks in the pharmaceutical sub-sector for the period February 2020 – December 2022 with a total sample of 9 companies. The selection of data samples in this study was carried out by purposive sampling. Data analysis techniques were carried out using the Normality Test, the Mean Absolute Deviation (MAD) Test, the t-Test: Two-Sample Assuming Equal Variances. The results of research and statistical tests show that the TFM model is more accurate than the APT model because it is shown by the MAD TFM value which is smaller than the MAD APT and there is no significant difference in accuracy between the Arbitrage Pricing Theory (APT) method and the Three Factor Model (TFM). in estimating stock returns for pharmaceutical sub-sector companies listed on the IDX for the period February 2020 – December 2022.